DIGITALIZZAZIONE E STAMPA 3D DI UN MOSAICO A TECNICA BIZANTINA A SCOPO DOCUMENTATIVO E CONSERVATIVO - Rivola, Riccardo; Castagnetti, Cristina; Bertacchini, Eleonora; Casagrande, Francesca (Archeomatica, 2016)
The new technologies related to geomatics and informatics now offer significant applicative potentiality for the documentation of cultural heritage, both in terms of data acquisition and for all representation, dissemination and communication stages .The paper shows an application of high resolution laser scanning survey, with photogrammetry data integration, in order to create a digital 3D model of a portion of a Byzantine mosaic that is later reproduced by rapid prototyping technology.